An entrepreneur-driven technological innovation system for sustainable and inclusive international business: a case analysis of Lusophone-African MNEs. (11th April 2023) - Mulvey, Chris; Goncalves, Marcus
For a more responsible and inclusive technological innovation system (TIS), entrepreneurs should strategically frame the technological innovation field in which they are inserted with diversity, equity, and inclusion (DEI) and environmental, social, and governance (ESG) criteria in mind. The literature on TIS system functions that need to be stimulated to develop sustainable technologies that meet ESG criteria successfully is scant. A literature review from the past seven years was conducted to investigate the applicability of the TIS framework from a DEI and ESG perspective. A total of 29 semi-structured interviews were conducted with leading high-tech exporting companies in Angola and Mozambique to assess TIS in a socio-political and economically challenging environment. The study results show that the TIS framework marginally aligns with the DEI and ESG. It proposes a slight adaptation of TIS, focusing on the entrepreneur as a catalyst for sustainable and inclusive technological innovation.